Chinese phytopharmacology for gastritis - A systematic review of high-quality randomized controlled trials - Carla Cardiga; Alexandre Constantino; Catarina Fonseca; Daniela Silva; Isabel Teixeira; Jorge Magalhães Rodrigues (Pharmacological Research - Modern Chinese Medicine)
Introduction: Gastritis is a highly prevalent condition, often lifelong, affecting a substantial portion of the global population. It is estimated that over half of all people experience some degree of chronic gastritis, representing hundreds of millions of individuals worldwide. This systematic review evaluates the efficacy and safety of Chinese phytopharmacological interventions for chronic gastritis, including atrophic and non-atrophic subtypes. Methods: A systematic search was conducted across PubMed, Cochrane Library, Embase, ScienceDirect, and EuropePMC up to November 2024. Only high-quality randomized controlled trials (RCTs) (Jadad score ≥3) were included. Data on characteristics, interventions, comparators, dosages, and key findings interventions were extracted and synthesized. Results: Six RCTs involving 1,195 patients were included. For Helicobacter pylori-negative atrophic gastritis, Piwei Peiyuan prescription and Yiwei Xiaoyu granules significantly improved atrophy and intestinal metaplasia (e.g., Piwei Peiyuan: 64 % improvement in gastric angle atrophy, p = 0.034). In H. pylori-positive cases, Weiwei granules + quadruple therapy achieved higher eradication rates and better histological outcomes than conventional treatment alone. In non-atrophic gastritis, Qirui Weishu capsules led to greater symptom resolution than Sanjiu Weitai (p < 0.01), and Houtou Jianweiling tablets were comparable to omeprazole in efficacy and safety. Conclusion: High-quality evidence from RCTs indicates that several Chinese herbal formulations—such as Piwei Peiyuan prescription, Yiwei Xiaoyu granules, and Qirui Weishu capsules—are effective in alleviating symptoms and improving histopathological outcomes in chronic gastritis, with safety profiles comparable to conventional treatments. These findings support the clinical potential of Chinese phytopharmacology, particularly in improving histological outcomes and alleviating symptoms like epigastric pain and dyspepsia, as standalone or adjunctive therapy. However, these results should be interpreted with caution due to variations in dosing, limited placebo use, and short follow-up periods across studies